First Field Release of a Genetically Engineered, Self-Limiting Agricultural Pest Insect: Evaluating Its Potential for Future Crop Protection - Shelton, Anthony M.; Long, Stefan J.; Walker, Adam S.; Bolton, Michael; Collins, Hilda L.; Revuelta, Loïc; Johnson, Lynn M.; Morrison, Neil I. (Frontiers in Bioengineering and Biotechnology, 2020)
Alternative, biologically-based approaches for pest management are sorely needed and one approarch is to use genetically engineered insects. Herein we describe a series of integrated field, laboratory and modeling studies with the diamondback moth, Plutella xylostella, a serious global pest of crucifers. A ‘self-limiting’ strain of Plutella xylostella (OX4319L), genetically engineered to allow the production of male-only cohorts of moths for field releases, was developed as a novel approach to protect crucifer crops Wild-type females that mate with these self-limiting males will not produce viable female progeny. Our previous greenhouse studies demonstrated that releases of OX4319L males lead to suppression of the target pest population and dilution of insecticide-resistance genes. We report results of the first open-field release of a non-irradiated, genetically engineered self-limiting strain of an agricultural pest insect. In a series of mark-release-recapture field studies with co-releases of adult OX4319L males and wild-type counterparts, the dispersal, persistence and field survival of each strain were measured in a 2.83-ha cabbage field. In most cases, no differences were detected in these parameters. Overall, 97.8% of the wild-type males and 95.4% of the OX4319L males recaptured dispersed < 35 m from the release point. The predicted persistence did not differ between strains regardless of release rate. At the release rate of 1,500, 90% of OX4319L males released would be expected to be recaptured 5.4 – 7.1 days after release. Moth strain had no effect on field survival but release rate did. Collectively, these results suggest similar field behavior of OX4319L males compared to its wild-type couterpart. Laboratory studies revealed no differences in mating competitiveness or intrinsic growth rates between the strains and small differences in longevity. Using results from these studies, mathematical models were developed that indicate release of OX4319L males should offer efficacious pest management of P. xylostella. Further field studies are recommended to demonstrate the potential for this self-limiting P. xylostella to provide pest suppression and resistance management benefits, as was previously demonstrated in greenhouse studies.